2014
DOI: 10.1108/jocm-07-2013-0125
|View full text |Cite
|
Sign up to set email alerts
|

Principal preparation in Kenya, South Africa, and Canada

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…As indicated in Table 2, there were numerous studies of leader preparation (e.g. Amakyi and Ampah-Mensah, 2013;Bush et al, 2011;Bush and Oduro, 2006;Onguko et al, 2008Onguko et al, , 2012Webber et al, 2014) and professional development (e.g. Bolden and Kirk, 2009;DeJaeghere et al, 2009;Ibara, 2014;Lassibille, 2016;Mathibe, 2007;Moorosi and Bush 2011;Otunga et al, 2008).…”
Section: Research Topicsmentioning
confidence: 99%
“…As indicated in Table 2, there were numerous studies of leader preparation (e.g. Amakyi and Ampah-Mensah, 2013;Bush et al, 2011;Bush and Oduro, 2006;Onguko et al, 2008Onguko et al, , 2012Webber et al, 2014) and professional development (e.g. Bolden and Kirk, 2009;DeJaeghere et al, 2009;Ibara, 2014;Lassibille, 2016;Mathibe, 2007;Moorosi and Bush 2011;Otunga et al, 2008).…”
Section: Research Topicsmentioning
confidence: 99%
“…The leaders were from the most populous and cosmopolitan county in Kenya. The interviews provided in-depth descriptions and raised pertinent issues that were not included in prior publications based on the questionnaire (Okoko et al, 2015;Scott et al, 2013;Webber et al, 2014). Three leaders were purposively selected from each of the following categories within the education system: levels of basic education (primary and secondary); types of schools (public and private); and socioeconomic groups (schools serving low-, middle-, and high-income communities).…”
Section: Methodsmentioning
confidence: 99%
“…The reason is that some individuals advance to the leadership position because of their satisfactory performance in the organizations but lack the type of training to help them adjust their behavior and attitude to lead organizational changes. 15 Webber et al 16 explored the role of inclusive leadership in the preparation and adoption of an International Study of Principle Preparation in three different countries. The authors considered prior leadership experiences, problematic leadership responsibilities, and perceived level of leadership preparation experiences in change processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They identified that cultural differences and individual exposure to psychosocial challenges, such as poverty, war, and crime affect the ability to practice inclusive leadership. 16 Webber et al 16 pointed out that providing leadership development training through programs like internships improves the skills of leaders to take charge of roles for fulfilling the functions of organizations.…”
Section: Literature Reviewmentioning
confidence: 99%